Thermal robustness of magnetic tunnel junctions with perpendicular shape anisotropy. Issue 11 (5th March 2020) - Lequeux, S.; Perrissin, N.; Grégoire, G.; Tillie, L.; Chavent, A.; Strelkov, N.; Vila, L.; Buda-Prejbeanu, L. D.; Auffret, S.; Sousa, R. C.; Prejbeanu, I. L.; Di Russo, E.; et al.
Abstract : Perpendicular Shape Anisotropy based storage layer offers a bulk anisotropy much more robust against thermal fluctuations than the interfacial anisotropy, allowing to reduce the temperature dependence of the coercivity of sub-20 nm MTJ cells. Abstract : The concept of Perpendicular Shape Anisotropy STT-MRAM (PSA-STT-MRAM) has been recently proposed as a solution to enable the downsize scalability of STT-MRAM devices beyond the sub-20 nm technology node. For conventional p-STT-MRAM devices with sub-20 nm diameters, the perpendicular anisotropy arising from the MgO/CoFeB interface becomes too weak to ensure thermal stability of the storage layer. In addition, this interfacial anisotropy rapidly decreases with increasing temperature which constitutes a drawback in applications with a large range of operating temperatures. Here, we show that by using a PSA based storage layer, the source of anisotropy is much more robust against thermal fluctuations than the interfacial anisotropy, which allows considerable reduction of the temperature dependence of the coercivity. From a practical point of view, this is very interesting for applications having to operate on a wide range of temperatures ( e.g. automotive −40 °C/+150 °C).